Cost estimation of "coal-to-gas" project: Government and residents' perspectives. (August 2022) - Li, Hui; Zhang, Ruining; Ai, Xianneng
Abstract: China is implementing "coal-to-gas" project, which plays a significant role in improving the environment, optimizing the energy structure, and building a beautiful China. To provide references for optimizing subsidy standards and promoting the implementation of "coal-to-gas" project, this study analyzes the cost and burden under different subsidy scenarios by establishing a cost estimation model from government and residents' perspectives. According to the estimation results, the cost of "coal-to-gas" project occupies up to 16% of the general public revenue for the low-income city. Due to the high cost of the energy transition, the heating expenditure after subsidy consistently obsesses the low-income households, which even accounts for 16% of disposable income (residents' burden) in the less-developed city. To improve the subsidy efficiency, it is supposed to increase the subsidy standards in cities with a higher residents' burden and reduce it in cities with lower residents' burden. The subsidies are suggested to be tilted towards low-income households and cities with low government revenue. Highlights: "Coal-to-gas" project causes high costs for both local government and residents. The effects of "coal-to-gas" subsidy reduction differ among regions. Subsidies are suggested to be appropriately reduced in high-income areas. Subsidies are suggested to be tilted towards low-income households.